AN ANALYSIS OF GRICEâS MAXIMS VIOLATION IN DAILY CONVERSATION - Fahmi, Rizal (IKIP Mataram, 2016)
This research were aimed at finding out what factors that cause the violation of Gricean maxims and which one of Gricean maxims that is often violated in daily conversation of EZC students of FPBS IKIP MATARAM. There were 15 active EZC students were taken as subject of the study. In deciding samples, purposive sampling technique was used. The samples were 4 male students and 5 female students. In the data analysis, descriptive qualitative method was used. For collecting data, there were 2 techniques used: observation and interview. After the data were collected, the recorded conversations (the length of each conversation is about 5 until 10 minutes) were sorted and translated. The result showed that the maxims violated were maxim of quantity (30 times), maxim of quality (20 times), maxim of manner (10) and maxim of relevance (5 times). The reason for violating the maxims approved to be caused by cultural factor and social distance factor. In conclusion, the maxim that dominantly being violated was maxim of quantity. Â